The use of Thiocetam in the complex therapy of combat-related brain contusion - I. F. Bielenichev; K. Yu. Nerianov; V. I. Chernii; D. A. Sereda; L. I. Kucherenko; N. V. Derevianko; К. І. Kandybei (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Each patient presents a unique set of characteristics and challenges when it comes to acute cerebral ischemia resulting from craniocerebral injury.